Effect of equi-molar dietary betaine and choline addition on performance, carcass quality and physiological parameters of pigs. - Siljander-Rasi, Hilkka; Peuranen, Seppo; Tiihonen, Kirsti; Virtanen, Erkki; Kettunen, Hannele; Simmins, P. Howard (British society of animal science, 2003)
Betainen and its precursor choline were compared in their efficaly in affecting the performance, carcass traits, and liver betaine concentration of growing-finishing pigs. Individually penned Finnish Landrace and Yorkshire pigs and their crosses (30 kg; no.=70) were offered the basal diet with no added betaine or choline, or the basal diet supplemented with low to moderate doses (250, 500 or 1000 mg/kg) of betaine (Betafin (R) S1), or with a similar molar amount of choline (578, 1155 or 2310 mg/kg of choline chloride). The maize-soya-bean-meal basal diet was formulated to contain 12.3 MJ/kg digestible energy, 155 g/kg crude protein and 7.4, 4.4 and 4.3 g/kg digestible lysine, threonine and methionine + cystine, respectively. Oat hull meal (100 g/kg) was added to reduce the diatary energy concetration. The pigs were on a restricted feeding level, 1.5 to 3.0 kg food per day (proportionally 0.8 of ad libitum intake) for 75 days. Daily weight gain and food-to-gain ratio improved linearly (P < 0.01) with increasing diatary betaine. Carcass weight increased linearly (P < 0.01) but slaughter loss proportion, backfat and sidefat thicknesses and lean proportions in ham and carcass were unaffected by dietary betaine level. Linear betaine level increased linearly (by up to a proportion of 0.62 in comparison with the control) with dietary betaine addition (P < 0.05) and betaine tended to improve linearly the tensile strengt of the proximal ileaum (P = 0.07). The presence of choline had no effect on any of the parameters. these results indicate that low to moderate doses of dietary betaine improved the growth and the efficiency of food utilization of growing-finishing pigs. Pigs on betaine diets had heavier carcasses without a relative increase in carcass fat. Choline had no such effects in pigs offered the restricted amount of diet. Liver betaine concentration increased with level of betaine in the diet whereas the betaine precursor choline did not affect hepatic betaine.
Keywords: Ko; pigs; betaine; choline